2023
DOI: 10.1002/brb3.3240
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of peripheral mean platelet volume in patients with mental disorders: Comparisons in depression, anxiety, bipolar disorder, and schizophrenia

Zhichao Chen,
Jing Wang,
Ciriaco Carru
et al.

Abstract: BackgroundThere is a growing interest in the role of immune and inflammatory responses in mental disorders (MDs). Mean platelet volume (MPV) is an extensively utilized hemogram parameter that reflects systemic inflammation and immune function. Our research sought to determine whether a connection exists between MPV and various types of MDs.MethodsWe searched PubMed, EMBASE, PsychINFO, and Web of Science for eligible studies from inception to 15 February 2023, supplemented by manual searching the references fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…In a recent study, mean platelet component levels, serving as an indirect measure of platelet activation, demonstrated a significant reduction following administration of atypical antipsychotics, indicative of increased platelet aggregation. 9 However, this study included only 16 patients and did not General Psychiatry 20 and can be used as a surrogate biomarker of platelet activity because of the greater activity of larger platelets, exhibited significantly higher MPV levels in patients taking atypical antipsychotic drugs compared with those in drug-naïve patients. 10 Conversely, Lee et al found no significant MPV changes in 100 patients with schizophrenia receiving clozapine for 1 year.…”
Section: Main Findingsmentioning
confidence: 99%
“…In a recent study, mean platelet component levels, serving as an indirect measure of platelet activation, demonstrated a significant reduction following administration of atypical antipsychotics, indicative of increased platelet aggregation. 9 However, this study included only 16 patients and did not General Psychiatry 20 and can be used as a surrogate biomarker of platelet activity because of the greater activity of larger platelets, exhibited significantly higher MPV levels in patients taking atypical antipsychotic drugs compared with those in drug-naïve patients. 10 Conversely, Lee et al found no significant MPV changes in 100 patients with schizophrenia receiving clozapine for 1 year.…”
Section: Main Findingsmentioning
confidence: 99%
“…Additionally, MPV has gained interest as a biomarker in other systemic inflammatory or chronic disorders [3]. For example, disrupted MPV values have been linked to mental disorders [4], cardiovascular disease [5] and cancer [6].…”
Section: Introductionmentioning
confidence: 99%